The Poverty Challenge in Africa: Innovative Cooperativism through Political Incentives. A Case Study of Nigeria - Akanji, Ajibola Anthony (Cooperativismo & Desarrollo, 2020)
This work, with the use of Nigeria as a case study, seeks to highlight a mode of redirecting Africa’s resources in solving the problem of poverty currently experienced by the continent. It focuses on the restructuring of humans and rechanneling of material resources. Using descriptive analysis as the method of research, it examines relevant data and attempts to make two fundamental and justifiable claims. The first claim is that “innovative cooperativism”, a uniquely developed form of economic socialization of the people in the form of collective self-help, built around the ideas of cooperation, cooperatives and solidarity economics, should be at the centre of breaking the enduring circle of African poverty; a strand of poverty which has often shown resistance to development. Although innovative cooperativism is a viable concept in addressing the poverty challenge and mobilisation for development, the concept is yet to be embraced by a significant section of Nigerian people, cooperatives, mutual and self-help groups due to the absence of political incentives. The second claim responds to the first by proposing that the three tiers of the Nigerian government should ensure a policy of benevolent but strict and disciplined welfarism in the form of political incentives to its development drives, anchored onto innovative cooperativism. Thus, contemporary poverty challenges in Nigeria are addressed through a system of standardised political incentives to the responsive mode of self-help on the part of the people, creating an effective synergy of government and people, thereby combating poverty at its very roots.